Transparansi dan Akuntabilitas dalam Pengelolaan Keuangan Negara - Lestari Sitorus; Nurullaeli Uswatun H; Suci Ananda Sitompul; Nazwa Feryal Kamila; Wahjoe Pangestoeti (Masyarakat Ekonomi Syariah Bogor, 2025)
State financial management is an important aspect in realizing good governance, including revenue, expenditure, debt management, and state assets. Transparency and accountability are the main pillars to ensure that state finances are managed effectively, efficiently, and in accordance with the principles of public accountability. The increasing demands of the community for openness and responsibility in state financial management reflect the importance of reform in the budget management system. However, the implementation of the principles of transparency and accountability often faces challenges, such as limited technology, human resource capacity, and organizational culture that is not yet fully supportive.